Faktor-faktor Penentu Keberhasilan Manajemen Keuangan pada UMKM - Sriningsih, Endang; Mustamin, Icha; Ramlah (Melati Institute, 2024)
This research aims to examine and analyze the influence of financial literacy, access to financing, use of information technology, and managerial competence on the success of financial management of MSMEs in South Sulawesi. This research uses quantitative methods with a survey approach, involving 200 MSMEs as samples. Data was collected through a questionnaire which was then analyzed using AMOS statistical software. The research results show that: (1) Financial literacy has a significant influence on MSME financial management, namely confirming that a good understanding of financial principles is very important to improve the quality of MSME financial management. (2) Access to financing and the use of information technology have also been proven to have a significant impact, namely being able to help MSMEs meet working capital and investment needs and then increasing operational efficiency and accuracy of financial reports. (3) The use of information technology supports financial management by increasing data accuracy and financial process efficiency, which can contribute significantly to the success of financial management. Good management requires adequate managerial skills to plan, manage risks and evaluate financial performance. Based on the research results, it is recommended that MSMEs improve their financial literacy through training and education. In addition, expanding access to formal financial services and the adoption of information technology must be encouraged to support better financial management. These findings provide valuable insights for policy makers and stakeholders in designing more effective support programs, to improve the success of MSME financial management in South Sulawesi.